Isolation and Characterization of Nodule-Associated Exiguobacterium sp. from the Root Nodules of Fenugreek (Trigonella foenum-graecum) and Their Possible Role in Plant Growth Promotion - Geetha Rajendran; Maheshwari H. Patel; Sanket J. Joshi (International Journal of Microbiology)
One of the ways to increase the competitive survivability of rhizobial biofertilizers and thus achieve better plant growth under such conditions is by modifying the rhizospheric environment or community by addition of nonrhizobial nodule-associated bacteria (NAB) that cause better nodulation and plant growth when coinoculated with rhizobia. A study was performed to investigate the most commonly associated nodule-associated bacteria and the rhizospheric microorganisms associated with the Fenugreek (Trigonella foenum-graecum) plant. Isolation of nonrhizobial isolates from root nodules of Fenugreek was carried out along with the rhizospheric isolates. About 64.7% isolates obtained from Fenugreek nodules were gram-negative coccobacilli, 29.41% were gram-positive bacilli, and all rhizospheric isolates except one were gram-positive bacilli. All the isolates were characterized for their plant growth promoting (PGP) activities. Two of the NAB isolates M2N2c and B1N2b (Exiguobacterium sp.) showed maximum positive PGP features. Those NAB isolates when coinoculated with rhizobial strain—S. meliloti, showed plant growth promotion with respect to increase in plant’s root and shoot length, chlorophyll content, nodulation efficiency, and nodule dry weight.